Uterine Rupture in Pregnancy following Fall from a Motorcycle: A Horrid Accident in Pregnancy—A Case Report and Review of the Literature - Wondimagegnehu Sisay Woldeyes; Demisew Amenu; Hailemariam Segni (Case Reports in Obstetrics and Gynecology)
Uterine rupture is one of the most catastrophic complications during pregnancy. It is a rare complication in developed countries but a frequent cause of maternal and perinatal morbidity and mortality in Africa. Uterine rupture occurs in 1.6% of patients suffering blunt abdominal trauma. Here we report a unique case of complete fundal rupture of the unscarred uterus following fall from motorcycle in 39-week-pregnant mother who was managed with total abdominal hysterectomy and left salpingo-oophorectomy and survived, though fetus died before intervention. We also reviewed similar cases reported from different parts of Africa. This is a preventable complication had the woman been properly instructed on transportation safety during her antenatal care visits.